Effect of graphene modified by a long alkyl chain ionic liquid on crystallization kinetics behavior of poly(vinylidene fluoride). Issue 112 (29th October 2015) - Hu, Yadong; Xu, Pei; Gui, Haoguan; Yang, Shanzhong; Ding, Yunsheng
Abstract : To investigate the effects of graphene (Gra) modified by 1-hexadecyl-3-methylimidazolium bromide (IL) on the crystallization kinetics behaviour of PVDF, a series of PVDF/IL blend, PVDF/Gra and PVDF/IL/Gra nanocomposites were prepared. Abstract : To investigate the effects of graphene (Gra) modified by a long alkyl chain ionic liquid (1-hexadecyl-3-methylimidazolium bromide, IL) on the crystallization kinetics behavior of poly(vinylidene fluoride) (PVDF), a series of PVDF/IL blend, PVDF/Gra and PVDF/IL/Gra nanocomposites have been prepared using a solution-cast method. The crystallization kinetics and corresponding crystal structure have been investigated using differential scanning calorimetry (DSC), polarized optical microscopy (POM) and X-ray diffraction spectroscopy (XRD). The crystallization kinetic parameters, such as relative crystallinity ( X t ), crystallization half time ( t 1/2 ), crystallization rate constant ( Z ), Avrami exponents ( n ) and activation energy ( E a ), have been determined by both isothermal and non-isothermal techniques. In the isothermal and non-isothermal crystallization process, for PVDF/0.5IL/0.5Gra, IL and Gra can facilitate nucleation to decrease E a ; moreover, the synergistic efforts of IL and Gra can maintain appropriate crystallization rate to form the β phase extruded form the α phase. The positive effect on the crystallization of PVDF may be ascribed not only to the existence of Gra–cation interaction between the imidazolium cation and the aromatic carbon ring structure, but also to the electrostatic interaction between the CF2 group of the polymer backbone and imidazolium cation.